Content marketing as a tool to disseminate concrete innovations (Research, Society and Development, 2021)
Brazil has expanded its means of scientific dissemination and is being transformed by the digital age that is being built in a variety of social spheres. The development of content and its dissemination on digital platforms has become an efficient strategy for professionals from different sectors. Scientific studies have constantly focused on the development of new technologies covering concrete, triggering multiple possibilities for its application. In this context, this article aims to demonstrate that scientific dissemination related to concrete innovations can be developed through content marketing. From a qualitative approach, a bibliographical survey was carried out for theoretical basis, as well as a critical analysis, in addition to quantitative methods for obtaining general data through the Not Just Analytics program. Based on Instagram's engagement metrics for the Construction + project, 4 posts were selected that enabled the analysis of public interactions. As a result of the performed analyses, it was found that the profile engagement rate was in the order of 4.27%; the average of likes per publication was equal to 30 and the average of comments equal to 6; the frequency of posts was 4.17 days; and, finally, the most used hashtags in publications are presented. Therefore, it appears that the project clearly uses content marketing as a tool to create lasting relationships and bring scientific knowledge, more specifically related to civil construction, providing its users with a clear and easy-to-understand language.